PENGARUH METODE ROLE PLAYING TERHADAP KETERAMPILAN KERJASAMA DAN KOMUNIKASI SISWA DALAM PEMBELAJARAN IPAS BERBASIS KURIKULUM MERDEKA DI KELAS VB SDN 7 WONOGIRI - Nindialisma, Thera Cetiya; Sadtyadi, Hesti; Ngadat, Ngadat (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Cooperation and communication skills are essential in developing the social competencies of elementary school students, aligning with the Pancasila Student Profile promoted in the merdeka curriculum. This study aims to describe the development of cooperation and communication skills of grade VB students at SDN 7 Wonogiri in IPAS learning through the role playing method. The research was conducted as Classroom Action Research (CAR) over two cycles spanning four weeks, involving 31 grade VB students divided into six groups based on economic roles. Data were collected through observations of cooperation skills (13 indicators) and communication skills (7 indicators), supported by pretest and posttest assessments. The analysis included data reduction, grouping, interpretation of observations per cycle, presentation in narrative or tabular form, and drawing conclusions. The results showed an improvement in cooperation from an average of 39.6 (76.2%) to 49.3 (94.8%), reflected in students’ ability to share tasks, actively contribute, and resolve differences constructively. Communication also increased from 20 (71.4%) to 25 (89.3%), although confidence in speaking before the class was not yet evenly distributed, students began to engage fluently in dialogue and use IPAS terminology accurately. The study concludes that role playing effectively enhances cooperation and communication skills, while supporting the implementation of the merdeka curriculum focused on developing 21st-century competencies. ABSTRAKKeterampilan kerjasama dan komunikasi penting dalam membangun kompetensi sosial siswa sekolah dasar, selaras dengan Profil Pelajar Pancasila pada kurikulum merdeka. Penelitian ini bertujuan mendeskripsikan perkembangan keterampilan kerjasama dan komunikasi siswa kelas VB SDN 7 Wonogiri dalam pembelajaran IPAS melalui metode role playing. Penelitian dilaksanakan dalam bentuk PTK dua siklus selama empat minggu dengan subjek 31 siswa kelas VB yang dibagi enam kelompok berdasarkan peran pelaku ekonomi. Data dikumpulkan melalui observasi keterampilan kerjasama (13 indikator) dan komunikasi (7 indikator), didukung pretest-posttest. Analisis mencakup reduksi, pengelompokan, interpretasi hasil observasi per siklus, penyajian narasi atau tabel, serta penarikan kesimpulan. Hasil menunjukkan peningkatan kerjasama dari rata-rata 39,6 (76,2%) menjadi 49,3 (94,8%), tercermin pada kemampuan berbagi tugas, berkontribusi aktif, dan menyelesaikan perbedaan pendapat. Komunikasi juga meningkat dari 20 (71,4%) ke 25 (89,3%), meski kepercayaan diri berbicara di depan kelas belum merata, siswa mulai lancar berdialog dan menggunakan istilah IPAS dengan tepat. Penelitian menyimpulkan role playing efektif meningkatkan keterampilan kerjasama dan komunikasi, sekaligus mendukung implementasi kurikulum merdeka berfokus keterampilan abad ke-21.